Testing a Neuro-Evolutionary Theory of Social Bonds and Addiction: Methadone Associated With Lower Attachment Anxiety, Comfort With Closeness, and Proximity Maintenance - Torres, Nuno (Frontiers in Psychiatry, 2019)
Evidence from non-human mammals for the involvement of the endogenous opioid system in prosocial behaviour is reasonably extensive and robust, however studies in humans are lacking. This study tests the neuro-evolutionary hypothesis that exogenous opiates, including morphine, heroine, and methadone, decrease separation anxiety and proximity by hijacking the neuro-peptide endogenous opioid system modulating social bonds. Participants were 486 subjects, 43% male, with ages between 18 and 62 years (M=26.4 ; SD=9.4), divided in 3 naturalistic groups: 1: addicts in drug-free treatment; 2: addicts in methadone programs; 3: normative non-clinical controls. Instruments: 1- Adult Attachment Scale (AAS; Collins & Read, 1990) composed of three subscales: Anxiety about being rejected (α= .83), Comfort with Intimacy (α = .68) and Comfort Depending on others (α = .70). 2- Caregiving Questionnaire (Kunce & Shaver, 1994) composed of four subscales: Proximity Maintenance: (α = .83.), Sensitivity: (α= .76), Controlling Caregiving (α = .77) and Compulsive Caregiving (α = 0.68). Results: MANCOVA models were computed; gender, age and education were included in the models. Methadone patients and Drug-free treatment addicts were equivalent and reported significantly lower Comfort depending others, Comfort with Intimacy and Caregiving Proximity. However Methadone users reported significantly lower Anxiety about being rejected than drug-free addicts, and were equivalent to non-clinical controls. In addition, correlations between the methadone intake dose and the questionnaires’ scales showed that dose was significantly and negatively correlated with Comfort with Closeness (rs=-.36; p<.01) and with Caregiving Proximity (rs=-.28; p<.05).